EVALUASI KEBIJAKAN PENDIDIKAN : Evaluasi Pembelajaran Daring - Dzaky Fauzan Abid; Farid Setiawan (LPPM STAI Muhammadiyah Probolinggo, 2022)
In the early months of 2019 the government officially announced that the COVID-19 outbreak had entered Indonesia. This has had a huge impact in many aspects, one of which is the world of education. To prevent the spread of COVID-19 cases, the government took quick action by eliminating learning at schools (offline). Instead, schools must prepare distance learning using technology (online). This online policy that is taken quickly will certainly cause polemics and problems in the reality on the ground. These polemics and problems should be evaluated so that the main problem solving can be found, so that learning can run well in the future.